The effects of nanosecond X-ray pulses on functional activity - I. R. Knyazeva; M. A. Medvedev; V. V. Ivanov; L. P. Zharkova; O. P. Kutenkov; V. V. Rostov; M. A. Bolshakov (Бюллетень сибирской медицины)
The effect of nanosecond pulses of X-ray (pulse repetition rate of 8—22 pulses per second, dose 0,3—1,8 mR per pulse) on the functional activity of isolated mitochondria of mice liver. The effects of changing the rate of oxygen consumption by mitochondria in different metabolic states of Chance and the degree of coupling of oxidation and phosphorylation were investigated. That effect depends on the parameters of exposure.